PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN PADA PT PERKEBUNAN NUSANTARAPERSERO (PTPN PERSERO) - Pasaribu, Aria Masdiana (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2016)
The Purpose of the research are: (1) to know CSR expenses and employee benefits partial effect to profitability of the PT Perkebunan Nusantara (PTPN), (2) to know CSR expenses and employee benefits simultan effect to profitability of the PT Perkebunan Nusantara (PTPN). The research was conducting by selecting of 11 company on the PTPN Persero in Indonesia, and using annual report in 2010-2012. The sample of this research collected by using purposived sampling. Analysis method is multiple regression method. The result of this research that corporate social responsibility expenses partial not influence to NPM, the same with the employee benefits partial not influence to NPM. But at the Corporate Social Responsibility expenses and employee benefits simultan positive influence to NPM.